Protective Effects of Selenium in Patients with Beta-Thalassemia Major - Ajand Aboutalebi; Abolghasem Jouyban; Hadi Chavoshi; Aliakbar Movassaghpour Akbari; Elnaz Shaseb; Parvin Sarbakhsh; Saba Ghaffary (Tabriz University of Medical Sciences, 2020)
Background: Beta-thalassemia major patients require repeated blood transfusion which is associated with iron overload in different organs such as heart, liver, kidney and their related complications. In this study the effects of selenium in iron overload related complications of patients with beta-thalassemia major were assessed. Methods: In this clinical trial, 34 beta-thalassemia major patients over 12 years old were enrolled. Patients with severe renal failure, history of selenium consumption over the last three months, change of blood transfusion pattern, and any change of chelating agent were excluded from the study. For all patients, tablet of selenium 200 µg/day was administered for a month. Blood samples were taken at baseline and after one-month to assess the level of ferritin, total iron-binding capacity (TIBC), aspartate aminotransferase (AST), alanine aminotransferase (ALT), serum creatinine (Scr), selenium. Hair loss was assessed by questionnaire before and after intervention. Results: From 34 patients, 27 (79.4%) had deficient level of selenium at baseline. The selenium level was increased after intervention (p=0.005). The level of serum ALT and Scr decreased remarkably after one-month selenium consumption (p=0.007 for both). In addition, the AST level decreased remarkably after intervention (p=0.053). Severe hair loss profile has improved significantly after supplementation (p=0.004). Conclusion: One-month selenium consumption improved liver and kidney function related markers remarkably. Moreover, selenium improved hair profile and severe hair loss in thalassemia patients. Further studies are needed on the effect of selenium administration on liver and kidney function.